Debate: Percutaneous revascularization strategies for distal left main coronary artery disease. Approach from the DKCRUSH-V trial - Antonio E. Gómez Menchero (REC: Interventional Cardiology (English Ed.), 2022)
QUESTION: What aspects do you think might explain the significant differences reported between the results from the EBC MAIN (European bifurcation club left main coronary stent study),1 and the DKCRUSH-V (Double kissing crush vs provisional stenting for left main distal bifurcation lesions) clinical trials?2 ANSWER: The EBC MAIN trial has proven the non-inferiority of the step-by-step provisional stenting technique approach compared to the early double stenting strategy in 467 patients with distal left main coronary artery bifurcation disease (Medina 1,1,1 or 0,1,1). No significant differences were reported regarding the overall rate of major adverse cardiovascular events, target lesion failure, acute myocardial infarction, and stent thrombosis.1 On the other hand, the DKCRUSH V trial randomized 482 patients with distal left main coronary artery bifurcation disease (Medina 1,1,1 or 0,1,1) to receive treatment with the provisional technique vs the DK-crush technique. The latter had a lower rate of major adverse cardiovascular events with statistically significant differences regarding target lesion failure (10.7% vs 5%) (hazard ratio, 0.42; 95% confidence interval, 0.21-0.85; P = .02), acute myocardial infarction (2.9% vs 0.4%; P = .03), and stent thrombosis (3.3% vs 0.4%; P = .02) at 1-year follow-up.2 Results were better in the most complex coronary bifurcation lesions...